Representation of the City in Traditional Chinese Gohua Painting: Motifs, Typology, Pictorial and Stylistic Features - Liu, Mingxuan (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The representation of the city in traditional Chinese painting has certain features and traditions that distinguish it from the representation of urban imagery in Western art. First of all, this is an artistic generalization of the urban landscape as part of the artistic context of nature. It is also important to focus attention on the depicted identities of the urban space (houses, streets, bridges, as well as the nature that surrounds the city, etc.). In addition to this, gohua in its historical development has an obvious tendency to panoramicity and a generalized way of perception, which actualizes a special system of artistic motifs. Within the historical context of Chinese painting, the city often has a symbolic meaning, and its visuality is represented through the symbolism of color, space or emblems. After all, the use of traditional artistic materials and techniques is of great importance, which determines the palette of artistic techniques and directly affects the artistic motifs of the representation of the city. The representation of the city within the gohua reflects the peculiarities of Chinese culture and perception of the world. Cities are considered as part of nature and interconnected with it. This approach gives works of art depth and symbolic meaning. It is substantiated that the cityscape in the context of the general phenomenology of guohua has its own conceptual and terminological niche, which can be translated as “urban ink painting” (都市水墨). In turn, within this niche, the most popular artistic technique is “meticulous painting” (gongbi /工笔画; literally, “working with a brush”).The following typical pictorial and stylistic features of the urban landscape genre within Chinese ink painting, which are characteristic of the modern stage of development of Chinese fine art, have been established: 1) Expressiveness, which is expressed in the artist’s effort to convey not only the appearance of the city landscape, but also the emotional reaction to the landscape; 2) Minimalism: the desire to build an artistic foundation with the minimum number of colors and elements and focus on the expressiveness of details; 3) Line graphics: as a sign reflects the European approach to understanding the technique and imagery of Chinese painting; in the urban landscape genre, it affects imagery by conveying the shapes and contours of objects; 4) Contrast, with the help of which artists create volume, depth and texture of the urban landscape; 5)A separate artistic parameter is symbolism, which is a field of interpretation of the general pictorial and stylistic repertoire.